Genetic diversity analysis of daluga (Cyrtosperma merkusii) using Sequence-Related Amplified Polymorphism in Siau, Sangihe and Talaud Islands, North Sulawesi, Indonesia - INA ERLINAWATI; ABINAWANTO ABINAWANTO; ANDI SALAMAH; RUGAYAH RUGAYAH (Biodiversitas Journal of Biological Diversity, 2018)
Erlinawati I, Abinawanto, Salamah A, Rugayah. 2018. Genetic diversity analysis of daluga (Cyrtosperma merkusii) using Sequence-Related Amplified Polymorphism in Siau, Sangihe and Talaud Islands, North Sulawesi, Indonesia. Biodiversitas 19: 2374-2380. Daluga or the giant swamp taro (Cyrtosperma merkusii (Hassk.) Schott, a member of Araceae, is one of the minor tuber crops in Indonesia. It has high nutritional value for alternative food. Sequences-Related Amplified Polymorphism (SRAP) primers combinations were used for the first time to assess the genetic diversity among 36 of daluga accessions from several locations in Siau, Sangihe and Talaud islands, North Sulawesi, Indonesia. All of the samples were successfully extracted from silica-gel dried leaves using CTAB methods with minor modifications. Using six SRAP primer combinations, a total of 80 DNA fragments were yielded, varied from 75-1500 bp. The scoring of the fragments resulted in 68 (85.03%) polymorphic bands. Amongst four populations studied, Siau Island population has the highest level of genetic variation with mean values of Na = 1.9375±0.2436, Ne = 1.6409 ± 0.3255, PPL = 93.75%, H = 0.3614 ± 0.1516 and I = 0.5299 ± 0.1978. Meanwhile, Salibabu, Talaud Island population has the lowest level of genetic variation with mean values of Na = 1.5125 ± 0.5030, Ne = 1.3075 ± 0.3723 , PPL = 51.25%, H = 0.1800 ± 0.1989 and I = 0.2700 ± 0.2855. The high of polymorphic bands were generated by SRAP markers suitable for further analysis method in applied and basic of the genetic study on Cyrtosperma species and also related genera. This new genetic information can be used for baseline data for further research especially to improving the variation of daluga and for the conservation of daluga in the future.